Respon Morfologi Tanaman Kedelai (Glycine max (L.) Merrill) Varietas Anjasmoro Terhadap Beberapa Iradiasi Sinar Gamma - Irwan Bonar Sibarani; Ratna Rosanty lahay; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2015)
Soybean was the self pollinated plant with low genetic diversity. The gamma irradiation was used toinduced the mutation as the genetic diversity. The increase of the genetic diversity would make theeasy selection of certain growth character. The effect of gamma irradiation on the first phase ofplant growth would affected the morphological performance and the plant yield. The aim of theresearch was to determine the morphological response of soybean plant (Glycine max (L.) Merill)Anjasmoro variety to the gamma irradiation. The research was priored by inducing the seed ofAnjasmoro variety with several gamma irradiation i.e. : 0, 100, 200, 300 gy. The result showed thatthe gamma irradiation affected the plant height, the number of branches, the time of flowering, theflower colouration, the time of pod maturation, the number of pods, the number of seeds, and theseed weight per plant.Keywords : Anjasmoro, Seeds, Gamma Ray Irradiation